FABRICATION AND CHARACTERIZATION OF ADVANCED MATERIALS AND COMPOSITES FOR ELECTROCHEMICAL SUPERCAPACITORS - Ata, Mustafa Sami (My University, 2017)
Electrochemical supercapacitors (ESs) have attracted great attention due to the advantages of long cycle life, high charge/discharge rate and high power density compared to batteries. Significant improvement in ES performance has been achieved via development of advanced nanostructured materials, such as MnO2 and composite MnO2-MWCNT and PPy-MWCNT electrodes. In this dissertation, advanced dispersants were developed and investigated for the dispersion, surface modification and electrophoretic deposition (EPD) of metal oxides, multiwalled carbon nanotubes (MWCNT) and polypyrrole (PPy) in different solvents. Nature-inspired strategies have been developed for the fabrication of MWCNT films and composites. The outstanding colloidal stability of MWCNT, dispersed using anionic bile acids, allowed the EPD of MWCNT. Composite MnO2-MWCNT films were obtained by anodic EPD on Ni plaque and Ni foam substrates. Good dispersion of MWCNT during Py polymerization was achieved and allowed the formation of PPy coated MWCNT. The film and bulk electrodes, prepared by EPD and slurry impregnation methods, respectively, showed high capacitance and good capacitance retention at high charge-discharge rates. The mechanisms of dispersion and deposition were investigated. Cathodic and anodic EPD of MWCNT, MnO2, Mn3O4 was achieved using positively and negatively charged dispersants. Co-deposition of MWCNT and MnO2 was performed using a co-dispersant, which dispersed both MWCNT and MnO2 in ethanol. Composite films were tested for ES applications. The efficient dispersion was achieved at relatively low dispersant concentrations due to strong adsorption of the dispersants on the particle surface, which involved the polydentate bonding. We found the possibility of efficient dispersion of MWCNT in ethanol using efficient anionic dispersants. The electrostatic assembly method has been developed, which offers the benefit of improved mixing of MnO2 and MWCNT. The use of different anionic and cationic dispersants allowed the fabrication of electrodes with enhanced capacitance and improved capacitance retention at high charge–discharge rates and high active mass loadings. The asymmetric devices, containing positive MnO2–MWCNT and negative AC–CB electrodes showed promising performance in a voltage window of 1.6 V. We proposed another novel concept based on electrostatic heterocoagulation of Mn3O4- MWCNT composites in aqueous environment. In this case, various dispersants were selected for adsorption and dispersion of MWCNT and Mn3O4 and this allowed the formation of stable aqueous suspensions of positively charged MWCNT and negatively charged Mn3O4, which facilitated the formation of advanced composites with improved mixing of the components. Testing results showed promising performance of Mn3O4–MWCNT composites for applications in electrodes of electrochemical supercapacitors.
Keywords: colloid; dispersion; manganese dioxide; hausmannite; carbon nanotubes; polypyrolle; electrophoretic deposition; heterocoagulation; super capacitor; asymmetric